High Voltage Electrical Injuries of Hand in Children Following Misuse of a Stainless Steel Wiper (Medical Forum Monthly, 2020)
Objective: To determine the association of common home floor wiper made up of stainless steel in high voltage electrical injuries of hand in children and to suggest solution for its prevention. Study Design: Descriptive / case series studyPlace and Duration of Study: This study was conducted at the Burns & Plastic Surgery Centre, Hayatabad Medical Complex Peshawar from April 2016 to October 2018.Materials and Methods: This descriptive case series study was carried out on 15 children < than 12 years who presented with high voltage electrical injury to the hand. Cases were admitted and resuscitated in emergency departments and further treated in a specialized hand unit. Thorough history including type and mechanism of injury was taken and examination findings were recorded. Photographs of the involved hand and wrist were taken and the parents were counseled for multi- stage operation.Results: There were 11 male and 4 female patients with an average age of 8.5 years. In all cases, mechanism of injury was contact of stainless steel wiper by the children with high tension electrical transmission lines while playing on roof top. In 4 cases, emergency faciotomy was performed somewhere else while in the remaining 11 cases, proper faciotomy of forearm and hand was performed by the primary surgeon. Hand involvements were 12 cases on the right and 3 cases on the left sides. Main procedures carried out were serial debridement (average 4 per patient), groin and abdominal flap coverage (13 patients), median and ulnar nerve grafting (9 patients), tendon transfers for median and ulnar nerves (11 patients), arthrodesis of wrist and CMC joints (4 Patients) and amputation (2 patients). The total span of treatment for reconstruction was on average 18 to 24 months.Conclusion: In our series, we found out that use of floor stainless steel wiper is the major cause of high voltage electrical injuries in pediatric population while playing on rooftop. It is recommended that use of stainless steel wiper should be discouraged and may be replaced by rubber and plastic or wood wipers to decrease the incidence of high voltage trauma. Also the bare electrical transmission lines should be insulated by plastic or rubber pipes when they run near to the roof top or boundary walls.